TINGKAT KEPUASAN KONSUMEN KUE TRADISIONAL “KIOS DANNY ANGGUR” DI PUSAT KULINER AIRMADIDI KABUPATEN MINAHASA UTARA - Alouw, Cindy Pricilia; Kumaat, Ribka M.; Olfie, Benu L. S. (AGRI-SOSIOEKONOMI, 2022)
The objective of this research is to determine the level of customer satisfaction of the Traditional Cake “Danny Anggur Stall” at the Airmadidi culinary center, North Minahasa Regency seen from the product, price, place, and service variables. This research was conducted from September to October 2021, using primary data and secondary data using accidental sampling technique as a sampling method and 30 respondents. The data analysis method used is descriptive data analysis using a Likert Scale. The results showed that the level of consumer satisfaction of traditional cake "Danny Anggur Stall" from the variables of product, price, place, and service was 71.67%, generally classified as satisfied. Specifically, the level of consumer satisfaction of the Traditional Cake “Danny Anggur Stall” which has the highest satisfaction index, namely the product variable is 73.61%, location is 73.33% and price is 70.74%. For the lowest satisfaction index, the place variable is 62.00%.